2009
DOI: 10.1002/ccd.22175
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular abdominal aortic stenosis treatment with the optimed self‐expandable nitinol stent

Abstract: In our small series, we observed that abdominal aortic stenosis can be successfully and effectively treated with OptiMed stents in the situations in which the stenotic segment is located next to the origins of the main visceral branches of abdominal aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…9 Although endovascular intervention of aortic stenosis is less invasive compared to surgical options, resulting in fewer procedural complications and lower mortality in patients with severe aortic gradients, surgical repair seems to be the first choice in the treatment of aortic coarctation when associated with aneurysmal degeneration, unfavorable anatomy, including severe occlusion of the aorta or extension to the aortic bifurcation and severe hypertension. 10 We also present here an incidentally detected mitral valve perforation (MVP) in an adult patient with undetermined cause. It is usually caused by infective endocarditis.…”
Section: Discussionmentioning
confidence: 88%
“…9 Although endovascular intervention of aortic stenosis is less invasive compared to surgical options, resulting in fewer procedural complications and lower mortality in patients with severe aortic gradients, surgical repair seems to be the first choice in the treatment of aortic coarctation when associated with aneurysmal degeneration, unfavorable anatomy, including severe occlusion of the aorta or extension to the aortic bifurcation and severe hypertension. 10 We also present here an incidentally detected mitral valve perforation (MVP) in an adult patient with undetermined cause. It is usually caused by infective endocarditis.…”
Section: Discussionmentioning
confidence: 88%
“…These are again encouraging but the authors stress the need for follow-up and outcome data (28,54,55) Optimal approaches for the management of pulmonary artery involvement in Takayasu arteritis remains to be determined and our approach has focused upon medical management. Successful surgical intervention has been reported and a variety of techniques have been employed.…”
Section: Management Of Aortic Coarctation In Takayasu Arteritis Is Pamentioning
confidence: 99%
“…4,14,45 More recent studies, however, solidify its role as a first-line intervention in select patients. [46][47][48][49][50] While a review by Delis and Gloviczki suggested that endovascular intervention largely be limited to focal aortic stenoses without branch arterial involvement, targeted endovascular interventions should be considered to alleviate symptoms specifically attributable to branch vessel disease. 8 If unsuccessful, these interventions do not preclude subsequent surgery.…”
Section: Angiography and Endovascular Interventionmentioning
confidence: 99%